The Use of Psychosocial Rehabilitation in Mental Health Issues - Asghar Dadkhah (Iranian Rehabilitation Journal, 2014)
Mental rehabilitation can include a range of disabling conditions, from severe and enduring psychotic or bipolar disorders to more transient affective disorders. The concept of rehabilitation reflects the concept of disability. If the concept of mental illness is viewed as a mechanism for social control, then we can say that one of the most powerful aspects of the medicalization of the individual is the application by physicians of diagnostic labels. It attempts to approach the issue of psychological rehabilitation (1-3) from a bio-psychosocial viewpoint, recognizing that a person’s physical, mental, motional, social and spiritual needs should be considered in the rehabilitation process. This multidisciplinary view focuses on recovery-oriented care of persons with mental health problems and on their rehabilitation program. An individual’s experience of a particular impairment needs to be understood within its social context and processes of socialization (4). Again here the role of psycho-rehabilitation programs will be magnetized in the mental health care (5).